It is raining mice and voles: which weather conditions influence the activity of Apodemus flavicollis and Myodes glareolus? - Wróbel, Aleksandra; Bogdziewicz, Michał (Springer, 2015)
Rodents constitute a crucial part of food chains in many ecosystems; thus, changes in their activity might influence many other species in the community. Moreover, daily variations in activity appear to be an important adaptation, helping rodents to cope with fluctuating intensity of predation pressure and food availability. We investigated how the nightly activity of the yellow-necked mouse (Apodemus flavicollis) and the bank vole (Myodes glareolus) changes with weather conditions. Increased cloud cover enhanced activity of mice, but this effect tended to be weaker during the full moon. In turn, the activity of bank voles was positively influenced by moon phase regardless of cloud cover. Temperature had a negative effect on the activity of both species. Rainfall positively influenced A. flavicollis capture numbers, but tended to decrease the activity of M. glareolus. Therefore, while the activity of both mice and voles was under a strong influence of weather variables, their responses to weather were largely species specific.
Keywords: Apodemus flavicollis; Myodes glareolus; Daily activity; Rodent activity; Small mammals; Weather conditions